Gamification as an alternative to increase students’ motivation: a scoping review - Rahmi, Iftita; Rimenda, Tetty; Ariyanti, Tika Dwi (Journal of Education and Learning (EduLearn), 2025)
Gamification is the process of adding game-like features and mechanics in non-game contexts, such as learning, training, or marketing, to make them more engaging, enjoyable, and effective. This scoping review aims to investigate the impact of gamification on student motivation and identify the most frequently used and effective elements of gamification in educational contexts. A systematic search was conducted using five databases: Emerald, Scopus, Sage, Garuda, and Google Scholar. The preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) guidelines were followed. The review included 25 articles that met the inclusion criteria. The findings suggest that gamification can positively influence student motivation and engagement. However, the effectiveness of gamification elements varies across different contexts and learners. Points, levels, and leaderboards are among the most commonly used elements, but their impact on intrinsic motivation remains debatable. The review highlights the need for further research to understand the specific factors that contribute to the success or failure of gamification in education. The insights gained from this review can serve as a foundation for developing effective gamification-based educational materials that cater to the diverse needs of learners and foster their motivation to learn.